Libraries in a digital age: access - Ball, Simon (Henry Stewart Talks, 2012)
Library access, Accessibility, Inclusion, Inclusive practice, Disability, Impairment, Technology, Barriers, Advocacy, Ethos, Library maturity, Innovation, Environment, Documentation, Best practice, Software, FOSS, Alternate formats, Policy, Benchmarking, Development